The Necessity of Nephrology Consultation for Critically Ill Patients with Acute Renal Failure - AR Lataifeh; Al-Ourani; T Gress; Z Khitan; F Zeid (Archives of Clinical Nephrology - Peertechz Publications, 2015)
Background: Acute renal failure (ARF) continues to be a challenging problem in critically ill patients. We reviewed the nephrology consultations in our ICU to assess the necessity of those consultations and if  there are any clinical criteria to indicate a necessary consultation. Methods: Retrospective chart review of nephrology consultations for patients with ARF in our medical ICU from 2010 to 2011. After data collection we classified consultations to necessary versus unnecessary based on an experts review. We used chi square and multivariate logistic regression model to compare both groups Results: We found that 45% of patients with ARF admitted to the ICU received nephrology consultation. 32% were identified as unnecessary. Age, gender and etiology were similar in both groups. Oliguria independently predicted the need for nephrology consultation Conclusions: Oliguria predicted the need for nephrology consultation independent of ARF etiology and could be utilized as a clinical guide for the necessity of nephrology consultation.